Place of Death among Cancer Patients in Brunei: A Retrospective Study - Ogechukwu Emmanuel; Venkatasalu Munikumar; Ani Afiqah Tuah (Golestan University of Medical Sciences, 2021)
Background: End of life and palliative care remains less popular and underdeveloped in many countries. Palliative care services have been proven to facilitate preference towards good death. The present study aimed to determine patterns and factors associated with place of death in Brunei Darussalam. Methods: This retrospective study was conducted in 2016 on all cancer deaths (n=801) recorded on the registry of death records in Brunei Darussalam. Data including sociodemographic characteristics and place of death were extracted from the medical records. Statistical analysis of data was done in SPSS 16 using binary logistic regression analysis at significance level of 0.05. Results: The overall number of cancer deaths increased from 171 in 2013 to 320 in 2015. The highest number of cancer deaths was recorded among those aged 50-59 (31%), 60-69 (22.6%), and 50-59 years (24.7%) in 2013, 2014, and 2015, respectively. Age and living in Temburong district significantly associated with the place of death (P<0.05). Conclusion: The location of specialized care settings associated with place of death among cancer patients. Our results may have important implication for development of specialized palliative and supportive care for end of life care.